If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + -6 = 2q Reorder the terms: -6 + 3p = 2q Solving -6 + 3p = 2q Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3p = 6 + 2q Combine like terms: -6 + 6 = 0 0 + 3p = 6 + 2q 3p = 6 + 2q Divide each side by '3'. p = 2 + 0.6666666667q Simplifying p = 2 + 0.6666666667q
| 50.45x+60=50.95 | | x^3+4x+80=0 | | -.07y-1.6=2.1y+1.2 | | 2x+3y=5x-2y+7 | | Kx(X-6)=2 | | .13x+X=20.34 | | 2.5r=120 | | 7.7a+11=72.6 | | 7+55x=33x+19 | | 5+5=2 | | (.2y)*y=.45 | | -8h+2h-10=-28 | | 3.5(-83x-3)=3.7(7x-30) | | 2x=3x-23 | | y=-16x^2+12x+0.2 | | x+29=51 | | y-5=-9(x-4) | | X^3y^2+3X^2y-28X=0 | | -0.72E-4= | | 12x^2+3x+8x+2= | | 3x+1+x+4=9-x | | 12+8x=5x+3 | | 8m^2-11m-10=0 | | 76=7+2x | | 69=23x | | 2(z-3)=4(3+x) | | -90+3=a | | -90+3= | | -(x-4)=3 | | (5+y)(3y+7)=0 | | 6-3c=6-3c | | 8(x+4)=6x+80 |